Serotonin is a common thread linking different classes of antidepressants - Witt, Colby E.; Mena, Sergio; Holmes, Jordan; Hersey, Melinda; Buchanan, Anna Marie; Parke, Brenna; Saylor, Rachel; Honan, Lauren E.; Berger, Shane N.; Lumbreras, Sara; Nijhout, Frederik H.; Reed, Michael C.; et al. (Cell chemical biology, 2023)
Depression pathology remains elusive. The monoamine hypothesis has placed much focus on serotonin, but due to the variable clinical efficacy of monoamine reuptake inhibitors, the community is looking for alternative therapies such as ketamine (neurogenesis theory of antidepressant action). There is evidence that different classes of antidepressants may affect serotonin levels; a notion we test here. We measure hippocampal serotonin in mice with voltammetry and study the effects of acute challenges of escitalopram, fluoxetine, reboxetine, and ketamine. We find that pseudo-equivalent doses of these drugs similarly raise ambient serotonin levels, despite their differing pharmacodynamics because of differences in Uptake 1 and 2, rapid SERT trafficking, and modulation of serotonin by histamine. These antidepressants have different pharmacodynamics but have strikingly similar effects on extracellular serotonin. Our findings suggest that serotonin is a common thread that links clinically effective antidepressants, synergizing different theories of depression (synaptic plasticity, neurogenesis, and the monoamine hypothesis).
Online verfügbar: 21. November 2023, Artikelversion: 21. Dezember 2023
Gesehen am 14.10.2024